The Phenotype and Genotype of Mevalonate Kinase Deficiency: A Series of 114 Cases From the Eurofever Registry. Issue 11 (27th October 2016) - ter Haar, Nienke M.; Jeyaratnam, Jerold; Lachmann, Helen J.; Simon, Anna; Brogan, Paul A.; Doglio, Matteo; Cattalini, Marco; Anton, Jordi; Modesto, Consuelo; Quartier, Pierre; Hoppenreijs, Esther; Martino, Silvana; et al.
Abstract : Objective: Mevalonate kinase deficiency (MKD) is a rare metabolic disease characterized by recurrent inflammatory episodes. This study was undertaken to describe the genotype, phenotype, and response to treatment in an international cohort of MKD patients. Methods: All MKD cases were extracted from the Eurofever registry (Executive Agency for Health and Consumers project no. 2007332), an international, multicenter registry that retrospectively collects data on children and adults with autoinflammatory diseases. Results: The study included 114 MKD patients. The median age at onset was 0.5 years. Patients had on average 12 episodes per year. Most patients had gastrointestinal symptoms (n = 112), mucocutaneous involvement (n = 99), lymphadenopathy (n = 102), or musculoskeletal symptoms (n = 89). Neurologic symptoms included headache (n = 43), cerebellar syndrome (n = 2), and mental retardation (n = 4). AA amyloidosis was noted in 5 patients, almost twice as many as expected from findings in previous cohorts. Macrophage activation syndrome occurred in 1 patient. Patients were generally well between attacks, but 10–20% of the patients had constitutional symptoms, such as fatigue, between fever episodes. Patients with p.V377I/p.I268T compound heterozygosity had AA amyloidosis significantly more often. Patients without a p.V377I mutation more often had severe musculoskeletal involvement. Treatment with nonsteroidal antiinflammatory drugs relieved symptoms. Steroids given during attacks, anakinra, and etanercept appeared to improve symptoms and could induce complete remission in patients with MKD. Conclusion: We describe the clinical and genetic characteristics of 114 MKD patients, which is the largest cohort studied so far. The clinical manifestations confirm earlier reports. However, the prevalence of AA amyloidosis is far higher than expected.